Late treatment with autologous expanded regulatory T-cell therapy after alemtuzumab induction is safe and facilitates immunosuppression minimization in living donor renal transplantation - Brook, MO; Hennessy, C; Hester, J; Hammad, S; Alzhrani, A; Rombach, I; Dutton, S; Lombardi, G; Wood, KJ; Friend, P; Harden, PN; Issa, F (Wolters Kluwer, 2024)
Background The TWO Study (Transplantation Without Overimmunosuppression) aimed to investigate a novel approach to regulatory T-cell (Treg) therapy in renal transplant patients, using a delayed infusion protocol at 6 mo posttransplant to promote a Treg-skewed lymphocyte repopulation after alemtuzumab induction. We hypothesized that this would allow safe weaning of immunosuppression to tacrolimus alone. The COVID-19 pandemic led to the suspension of alemtuzumab use, and therefore, we report the unique cohort of 7 patients who underwent the original randomized controlled trial protocol. This study presents a unique insight into Treg therapy combined with alemtuzumab and is therefore an important proof of concept for studies in other diseases that are considering lymphodepletion.